Prostate Tumor Overexpressed 1 Is a Novel Prognostic Marker for Hepatocellular Carcinoma Progression and Overall Patient Survival. Issue 4 (January 2015) - Chen, Shu-Peng; Zhang, Luo-Sheng; Fu, Bin-Sheng; Zeng, Xian-Cheng; Yi, Hui-Min; Jiang, Nan; Teksoz., Serkan
<x xml:space="preserve">Abstract</x> Abstract The gene prostate tumor overexpressed 1 (PTOV1) was first found to be upregulated in prostate cancer. This upregulation increased tumor cell proliferation, retinoic acid resistance, and migration. This study investigated the expression and prognostic significance of PTOV1 in hepatocellular carcinoma (HCC). Real-time Polymerase Chain Reaction and western blot analysis were performed to examine PTOV1 expression in 11 HCC cell lines and 2 normal hepatic cell lines. PTOV1 expression levels were also determined in 8 pairs of tissue samples taken from primary HCC tumors and the matched adjacent noncancerous liver tissue from the same patient. Immunohistochemistry assays assessed PTOV1 protein expression in paraffin-embedded clinical samples taken from 215 HCC patients. The correlation of PTOV1 expression with the clinicopathological parameters was evaluated along with the prognostic impact of PTOV1 expression in these HCC patients. PTOV1 mRNA and protein were overexpressed in HCC cell lines compared with normal liver cell lines and were overexpressed in primary HCC samples compared with the matched noncancerous liver tissue samples. In the paraffin-embedded tissue samples from 215 HCC patients, PTOV1 protein expression was significantly correlated with T classification, N classification, clinical stage, and serum α-fetoprotein. HCC patients with higher PTOV1 expression had shorter survival times than patients with lower PTOV1 expression. Our study demonstrated that PTOV1 overexpression is correlated with increased aggressiveness of HCC and could be a prognostic biomarker for patients with HCC.